Experimental study on the prospect of low-temperature heat to power generation using Trilateral Flash Cycle (TFC). (25th May 2020) - Iqbal, Md Arbab; Rana, Sohel; Ahmadi, Mahdi; Date, Abhijit; Akbarzadeh, Aliakbar
Highlights: TFC is a promising thermodynamic cycle for low grade heat to power generation. TFC system using organic working fluid and stationary CD nozzle with impulse turbine. TFC system can produce more power than ORC for same heat source. TFC system can utilize heat sources of below 80 °C. Integrating TFC system with existing ORC system can enhance power generation. Abstract: In this paper, a trilateral flash cycle (TFC) based system has been developed and studied to find out its prospect for utilizing more energy and enhancing the power generation capacity. To hold simplicity and minimize the cost of system construction, an impulse turbine and a converging-diverging (CD) stationary nozzle setup have been used as the expander. The experimental study introduced impulse turbine incorporates with a stationary CD nozzle and organic working fluid, which showed a promising power generation capability from a heat source below 80 °C in spite of the increasing size of the heat exchanger, condenser, and pump. In addition to the use of proper impulse turbines, however, the power generation capacity of such type of system is basically a function of the nozzle isentropic efficiency, which lies on the nozzle geometry and the alignment with respect to the turbine. A case study on the application of the TFC system for commercial power generation in associate with economic analysis has also been included in this study which shows a payback time less than 10 years with typical operational life of 20 years, considering only 40% nozzle isentropic efficiency and by using more efficient nozzle, the capital cost per unit power generation could be minimized.